Biochemical Markers in The Diagnosis and Prognosis of Cerebral Stroke - E. M.Tashkenov (Scholars Digest Publishing, 2023)
Acute stroke is one of the serious problems of modern medicine and Neurology. The death or disability of patients caused by a cerebral stroke has a negative impact on healthy morals and the state economy. According to the World Federation of neurologists (WFN), 14-16 million people around the world are registered with acute cerebral stroke every year, of which 5 million are fatal, 5mln patients are registered for disability. In Russia, 400-450000 people a year are sick with a stroke, which in every 1.5 minutes one patient is sick with a stroke.
Keywords: acute stroke, blood vessels, Matrix metaloprotease, nerve tissue.